Boundedness of weak solutions of a nondiagonal parabolic system of two equations - Portnyahin, D. V. (Ukrains’kyi Matematychnyi Zhurnal, 2009)
We study the problem of boundedness of weak solutions of a general nondiagonal parabolic system of nonlinear differential equations whose matrix of coefficients satisfies special structural conditions. To do this, we use a procedure based on the estimation of a certain function of unknowns.